Urgensi Diratifikasinya Konvensi 1951 Tentang Pengungsi Perspektif Hukum Keimigrasian - Tirza Siahaya; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Indonesia does not have any interest in relation to refugees because it has not become a party to the 1951 Convention and the 1967 Protocol. Therefore, the Indonesian government also does not have the authority to grant refugee status. so that the arrangement of problems regarding refugees is determined by the United Nations High Commissioner for Refugees (UNHCR), the UN agency which deals with refugee matters in accordance with the mandate it received under the UNHCR Statute of 1950.Purposes of the Research: The purpose of this study is the Urgency of Indonesia to ratify the Convention so that Indonesia has no difficulty dealing with refugees and there are clear and optimal rules regarding refugee issues. Methods of the Research: The research method used is juridical normative, the type of research is descriptive analytical, the source of the legal materials used are primary legal materials, secondary legal materials, and tertiary materials. The technique of collecting legal materials through literature study and then analyzed using qualitative methods.Results of the Research: Based on the results of the study, it was concluded that the urgency of Indonesia to ratify the Convention so that Indonesia would not have difficulty dealing with refugees and that there were clear and optimal rules regarding refugee issues because so far the issue of refugees was not regulated in the Immigration Act but only regulates immigrants. However, it indirectly regulates refugees. Therefore, the rules applied to refugees in Indonesia to date are Law Number 6 of 2011 concerning Immigration, but do not contain specific handling and provisions (lex specialis). So that refugees who enter Indonesian territory are treated with the same mechanism as legal immigrants who are accommodated in the Migration Detention Center (RUDENIM) whose facilities are classified as inadequate, of course this can cause psychological pressure for refugees, especially since Indonesia has ratified the UDHR. The next thing is that they are deported and even repatriated, of course this violates the principles contained in the 1951 Convention, where the legal protection for refugees by the Indonesian government uses the principles contained in the 1951 Convention. So indirectly Indonesia has followed the provisions of the 1951 Convention. Therefore, it is not allowed if there are refugees who are returned to their countries of origin.